Peran Bimbingan dan Konseling Dalam Menangani Kecemasan Pada Anak di Panti Asuhan Aisiyah - Fitri, Hidayatul; A, Afrinaldi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Counseling is a process of providing assistance provided by a counselor to a counselee who is experiencing problems, and also a process of interaction between the counselor and the counselee in order to find a bright spot for the counselee's problems. The aim of this research is the importance of the role of guidance and counseling for anxiety in children in orphanages. This research uses qualitative methods with data collection techniques through observation and interviews. There were four respondents, including the head of the Aisyiyah orphanage, one caregiver, and two foster children. The research results show that in particular caregivers and leaders have played a role in the process of providing guidance by guiding and developing foster children using the lecture method. The anxiety that children experience when they move to college, there are 2 children who experience very great anxiety, where they always think about where they will go from here. Counseling services must be provided so that children's anxiety does not drag on and can be resolved quickly and correctly.